NURSES’ PERCEPTION ABOUT PATIENT SAFETY CULTURE IN DUHOK HOSPITALS - BARWARI, RONAK HASSAN (Journal of Duhok University, 2021)
Background: Patient safety is one of the vital aspects that integrated to the health care system and patients’ outcomes. It is crucial to focus on the concept of patient safety to improve the health care services and the quality of care. The study was conducted to identify the variations in nurses’ safety attitudes based on their demographics. Methods: This is a cross-sectional study conducted among 100 nurses working in teaching hospitals at Duhok City/ Kurdistan region/Iraq. The data was collected using two parts survey: The Safety Attitude questionnaire and the demographics. The data were analyzed using the SPSS statistical software ver. 24, which included descriptive and inferential statistical analysis with a P-values ≤ 0.05. Findings: The study revealed that there was a statistically significant difference in nurses’ safety attitudes based on their level of education. The level of education and team working were correlated, and a significant correlation was found between working conditions and with nurses’ experience. Moreover, the study represented that there is no significant correlation between leadership role with safety variables. Conclusions: It is crucial to assess the factors that contribute to patients safety. To improve the quality of care and safety attitude, nurse leaders and stakeholders play an important role. Nurse leaders support the safe environment at the units of care. Moreover, focusing on achieving a higher level of education is crucial and recommended to enhance the Patients outcomes